ANALISIS KAPASITAS DAN TINGKAT PELAYANAN JALAN DI KORIDOR TIMUR KOTA PADANG - Raga Cipta Prakasih; Rahmanelli rahmanelli; endah Purwaningsih (JURNAL GEOGRAFI, 2014)
Abstract The purpose of this research is identify and analyze highway capacity and level of service at segment Alai Timur street, Ampang Raya street and Kampung Kalawi street of Padang City. This research use roads segment capacity, vehicle through volume, and side problem frequency. The primary source of data were capacity counting, volume, and side problem also use characteristic level of service as secondary source. The data was collected at four different places which 1) Simpang Alai, 2) Ampang, 3) Adzkia, and 4) Simpang By Pass. From places data was reach and count at capacity 9.677 PCU/hour and volume at 6784, 7308, 6894 dan 5608 PSU/hour. With this data obtained level of service coefficient was at range 0,58 – 0,75 with character vehicle mobility was dropping because of fluctuative vehicle volume, no free manuver and low passenger comfortability but still could handle daily vehicle movement, either on weekend and weekday. But in certain condition as mitigation disaster have not been confirmed.